Tepak Kendang Jaipong dalam Kesenian Campursari - Asep Saepudin Saepudin; Ela Yulaeliah (PANGGUNG, 2021)
This paper aims to determine the causes of changes in the Jaipong kendang motifs and analyze its motifs in Campursari. This writing uses the method of descriptive analysis. The entry of the Jaipong kendang in Campursari led to various changes from the original kendang. The conclusions obtained were changes in the multiple motifs of Jaipong kendang as a result of adjusting the Jaipong kendang to the Campursari performance. The Campursari players, who are predominantly Javanese and have traditional values, cannot be separated when they play the Jaipong kendang. The sense of tradition of the artists in playing the Javanese kendang, of course, indirectly channeled in the Jaipong kendang. The result is that new motifs of Jaipong kendang are the result of the artists’ creativity. Jaipong kendang motifs contained in Campursari, in general, are mincid motifs. It is found in almost every song accompanied by the Jaipong kendang. The other motifs are in the form of codes or accents made by artists as a unique feature in every Campursari song. Keywords: tepak, jaipong, mincid, campursari  ABSTRAK Tulisan ini bertujuan untuk mengetahui penyebab terjadi perubahan motif kendang jaipong serta menganalisis motif-motif kendang jaipong dalam Campursari. Metode deskriptif analisis digunakan dalam penulisan ini. Masuknya kendang jaipong dalam Campursari, menimbulkan berbagai perubahan dari kendang aslinya. Hasil kesimpulan diperoleh bahwa terjadinya perubahan beragam motif kendang jaipong sebagai akibat disesuaikannya kendang jaipong dengan sajian Campursari. Pemain Campursari yang mayoritas orang Jawa dan telah memiliki nilai tradisi, tidak lepas begitu saja ketika mereka memainkan kendang jaipong. Rasa tradisi para seniman dalam bermain kendang Jawa, tentunya secara tidak langsung tersalurkan di dalam kendang jaipong. Hasilnya adalah motif-motif baru kendang jaipong hasil kreativitas para seniman. Motif-motif kendang jaipong yang terdapat di dalam Campursari secara umum adalah motif mincid. Motif mincid ini terdapat hampir di setiap lagu yang diiringi kendang jaipong. Adapun motif lainnya adalah berupa kode atau aksen-aksen hasil karya seniman sebagai ciri khusus dalam setiap lagu Campursari.   Kata kunci: tepak, jaipong, mincid, campursari